Aplikasi Metode Spatial Multi Criteria Analisysis untuk Pengembangan Kawasan Permukiman (Studi Kasus: Re-Evaluasi RTRW Provinsi Sulawesi Tenggara) - Septianto Aldiansyah; Adi Wibowo (Jurnal Geografi, Edukasi dan Lingkungan (JGEL), 2022)
Southeast Sulawesi is a province that has become one of the destinations for transmigration and urbanization due to its low population density and abundant natural resources. This area is supported by the existence of supporting sectors such as agriculture, service industry, animal husbandry, fisheries, tourism and culture. This potential can lead to an increase in population and have an impact on increasing the need for residential land. Land suitability analysis is very important and relevant as a basis for reference in regional development to anticipate impacts that will occur in the future. This study aims to analyze and evaluate the suitability of residential areas in Southeast Sulawesi Province based on the RTRW of Southeast Sulawesi Province and the Regional Regulation of Southeast Sulawesi Province No. 2 of 2014. The method used is Spatial Multi Criteria Analysis (SMCA) because it excels in location determination analysis and decision making. The results show that there are 373,598.3 hectares of land in Southeast Sulawesi that are suitable and can be developed for residential areas. The evaluation of the RTRW found deviations in the actualization of spatial planning, especially in the Protected and Cultivated Areas. Therefore, this study can be used as an initial reference in re-evaluating the RTRW of Southeast Sulawesi Province.